A bottom-up acidification strategy engineered ultrathin g-C3N4 nanosheets towards boosting photocatalytic hydrogen evolution. (15th August 2020) - Wang, Longyan; Hong, Yuanzhi; Liu, Enli; Duan, Xixin; Lin, Xue; Shi, Junyou
Abstract: At present, graphene-like carbon nitride (g-C3 N4 ) has been considered as a promising photocatalyst for photocatalytic hydrogen gas (H2 ) evolution from water. The top-down treating of pristine bulk g-C3 N4 (CN–B) by strong acid is an efficient modification way to improve photocatalytic performance, yet this strategy is environmental unfriendly because it requires higher strong acid concentration. To this end, here we firstly developed an available bottom-up acidification strategy to prepare the 2D ultrathin g-C3 N4 nanosheets (UCNs) by the direct calcination of as-formed precursor derived from hydrothermal treating of melamine merely in diluted H2 SO4 solution. As a result, the engineered UCNs with an average thickness of approximately 3 nm exhibited a remarkably enhanced visible-light-driven photocatalytic H2 evolved rate of 2590 μmol g −1  h −1 ( λ  > 400 nm), which is over 9.9-folds and 2.2-folds larger than that of CN–B and acid-treated g-C3 N4 (CN-A) under the same condition, respectively. Our research offers a feasible and effective bottom-up acidification strategy for synthesizing the high-performance UCNs photocatalyst towards renewable solar energy conversion. Graphical abstract: Image 1